Previously unknown role for the ubiquitin ligase Ubr1 in endoplasmic reticulum-associated protein degradation - Stolz, Alexandra (National Academy of Sciences, 2013)
Quality control and degradation of misfolded proteins are essential processes of all cells. The endoplasmic reticulum (ER) is the entry site of proteins into the secretory pathway in which protein folding occurs and terminally misfolded proteins are recognized and retrotranslocated across the ER membrane into the cytosol. Here, proteins undergo polyubiquitination by one of the membrane-embedded ubiquitin ligases, in yeast Hrd1/Der3 (HMG-CoA reductase degradation/degradation of the ER) and Doa10 (degradation of alpha), and are degraded by the proteasome. In this study, we identify cytosolic Ubr1 (E3 ubiquitin ligase, N-recognin) as an additional ubiquitin ligase that can participate in ER-associated protein degradation (ERAD) in yeast. We show that two polytopic ERAD substrates, mutated transporter of the mating type a pheromone, Ste6* (sterile), and cystic fibrosis transmembrane conductance regulator, undergo Ubr1-dependent degradation in the presence and absence of the canonical ER ubiquitin ligases. Whereas in the case of Ste6* Ubr1 is specifically required under stress conditions such as heat or ethanol or in the absence of the canonical ER ligases, efficient degradation of human cystic fibrosis transmembrane conductance regulator requires function of Ubr1 already in wild-type cells under standard growth conditions. Together with the Hsp70 (heat shock protein) chaperone Ssa1 (stress-seventy subfamily A) and the AAA-type ATPase Cdc48 (cell division cycle), Ubr1 directs the substrate to proteasomal degradation. These data unravel another layer of complexity in ERAD.